PerCursos Vol. 12, n. 2 (2011) - Costa Junior, Maurício Pereira da (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2013)
PerCursos Vol. 12, n. 2 (2011)Link de acesso ao númerohttp://periodicos.udesc.br/index.php/percursos/issue/view/241